Eduwall Android App Development Superapps-Based for Simplicity Learning for Deaf Students - Mawardi Nurullah; Nisak Ruwah Ibnatur Husnul (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2023)
This research aims to develop an Android application called Eduwall based on the SuperApps framework for facilitating the learning process for deaf students. This study used a research and development (R&D) method, employing data collection techniques such as surveys, observations, interviews, and questionnaires to inform the development of the Eduwall application. The subjects in this research were deaf students at Pamulang University. The data analysis process encompassed six stages: concept development, design, material collection, assembly, product test and distribution. The research findings showed that the Eduwall application, based on the superapps model, was deemed suitable for use. This had been tested by IT experts, media experts, disability experts, lecturers, and students. The feasibility of this application means that the Eduwall application was practical, effective, efficient, and fun for students, especially deaf students. This Eduwall application was also equipped with a sign language dictionary to facilitate users in understanding the conditions of deaf students.